Experience of a Medical School in the Philippines on the Sudden Shift to Online Learning amidst COVID-19 - Baquiran, Raymundo S (Archīum Ateneo, 2022)
Introduction The COVID-19 pandemic forced educational institutions to adapt to a full online learning environment. Medical schools in particular were disrupted by this shift since the majority of the learning objectives, skills, and necessary competencies are learned through classroom and hospital face-to-face activities. Objective The purpose of this paper is to describe the experiences of a medical school in the country as it navigated the sudden shift to full online learning vis-à-vis a framework on the barriers and solutions to online learning. Method This is a descriptive paper written from the perspective and observations of an administrator who participated in crafting the immediate response of the school to the sudden shift to online delivery and who worked with the stakeholders of the Ateneo School of Medicine and Public Health (ASMPH). Results To address concerns on time, skills and infrastructure, the school reprioritized its learning objectives for the remainder of the school year. It conducted in-service sessions for faculty while also immediately setting up a learning management system and a technical support team that was available on demand. Strategies employed included a deliberate switch to asynchronous learning, curation of content and creativity in delivery and assessment, and the reshaping of the management and public health activities into the online platform. To manage attitudes and provide institutional support, the school worked collaboratively with stakeholders and transformed its traditional support services of campus ministry, counselling, formation, and physical and mental health to be readily available online. Conclusion We described the experience of ASMPH when medical schools were forced to completely shift to online delivery of their programs because of the pandemic. We identified the barriers and solutions of online learning in medical education. The unique context of the ASMPH for having a dual degree in medicine and management; having an inter-disciplinal, non-departmentalized set-up at each year level; and, possessing the traditions of Jesuit education were instrumental in the school’s ability to navigate this sudden shift.